Gaya Kepemimpinan Donald Trump dalam Kebijakan Deferred Action for Childhood Arrivals (DACA) pada Dreamers - Arini, Putrima; Moenir, Haiyyu Darman; Harza, Zulkifli (Hubungan Internasional Universitas Andalas, 2025)
The United States is the country with the highest immigrant population in the world, comprising 13.6% of its total population. The Deferred Action for Childhood Arrivals (DACA) policy, introduced by former President Barack Obama, was a measure aimed at reducing the number of illegal immigrants in the U.S. A significant majority of DACA recipients, approximately 81%, are originally from Mexico. Donald Trump sought to rescind the DACA policy established by Obama. This study aims to examine Donald Trump's leadership style in the context of the DACA policy rescission and its potential impact on international relations and the global image of the U.S. Trump perceived the presence of immigrants as an obstacle to his efforts to enhance the well-being of native-born Americans, necessitating measures to curb immigration in the U.S. The repeal of DACA faced opposition from various parties, who viewed it as a violation of human rights and financially detrimental to the U.S. Trump's role in the rescission of the DACA policy is analyzed using the conceptual framework of